HUBUNGAN ANTARA SPIRITUALITAS DAN RESILIENSI DENGAN TINGKAT DEPRESI PADA MAHASISWA FAKULTAS KEDOKTERAN UNIVERITAS PEMBANGUNAN NASIONAL VETERAN JAKARTA - Chintia (2022)
Depression is a mood disorder that causes distress and affects feelings, thought, and daily activities. Medical students belong to a group that is prone to depression. The high incidence of depression in medical students is caused by stressors in study loads and busy schedules, especially during the COVID-19 pandemic. COVID-19 affects mental health, including a significant increase in depression rates because everyone is required to adapt to constantly changing situations. Therefore, medical students need the role of spirituality and resilience as protective factors from the occurrence of depression which also allows medical students to rise when faced with difficulties. This study aims to determine the relationship between spirituality and resilience with the level of depression in medical students. This research was an observational analytic study with a cross-sectional approach. The research sample was 246 respondents by using Daily Spiritual Experience Scale (DSES), Connor-Davidson Resilience Scale (CD-RISC), and Beck Depression Inventory (BDI-II) questionnaires. From the results of this study, it was found that the prevalence of depression in respondents was 39%. The bivariate analysis using the Chi-Square test showed a relationship between spirituality with the level of depression (p=0.000) and resilience with the level of depression (p=0.000). Thus, it can be concluded from this study that there is a significant relationship between spirituality and resilience with the level of depression in medical students of Universitas Pembangunan Nasional Veteran Jakarta. The higher spirituality and resilience, the lower depression level and vice versa. The lower spirituality and resilience, the higher depression level.